PENGARUH FAST INTERVAL TRAINING (FIT) TERHADAP HASIL KECEPATAN RENANG GAYA BEBAS 100 METER PADA ATLET K.U II LUMBA-LUMBA SWIMMING CLUB BINJAI TAHUN 2021 - Amon Sandri Purba; Irwansyah Siregar (Journal Physical Health Recreation (JPHR), 2021)
This research was carried out at the Swimming Club Binjai Dolphins at the Tirta Raerim Mencharm swimming pool in the Peacock Meadows, North Sumatra. held on November 10 to January 28, 2021 for 8 weeks with a frequency of 2 times a week.This study aims to determine the effect of fast interval training (FIT) on the results of the 100 meter freestyle swimming speed for the K.U II Dolphin Swimming Club Binjai. The research method used in this study is an experimental method with a sample of 8 people with a purposive sampling research design. Then the sample did an initial test (pre-test), namely with a 100-meter swimming test, then the sample was given Fast Interval Training (FIT) training then after 8 weeks of programmed exercise the sample did a final test (post-test).The results of the analysis of the hypothesis, that there is a significant effect of fast interval training (FIT) training on the results of the 100 meter freestyle swimming speed for the K.U II Dolphin Swimming Club Binjai athletes. 2021 year. The results of the t-test obtained tcount = 0.3096 and t-table = 0.258. At the real level = 0.05 then t-count > t-table. Based on the hypothesis testing criteria, HO is rejected and Ha is accepted. Thus it can be concluded that there is a significant effect of Fast Interval Training (FIT) on the results of the 100 meter freestyle swimming speed for the KU II Lumba-lumba Swimming Club Binjai athletes 2021.